Acoustic radiation force impulse (ARFI) elastography of testicular disorders in dogs: Preliminary results - Feliciano, M. A.R. [UNESP]; Maronezi, M. C. [UNESP]; Simões, A. P.R. [UNESP]; Maciel, G. S. [UNESP]; Pavan, L. [UNESP]; Gasser, B. [UNESP]; Silva, P. [UNESP]; Uscategui, R. R. [UNESP]; Carvalho, C. F.; Canola, J. C. [UNESP]; Vicente, W. R.R. [UNESP] (FapUNIFESP (SciELO), 2016)
The aim of this study was to describe the use of acoustic radiation force impulse (ARFI) elastography in the evaluation of testicular disorders in dogs. Eighteen dogs with testicular disorders (thirty-six testicles) were assessed. Echotexture, size, contours and margins of testes were analysed by ultrasonography. Deformities and tissue stiffness (greyscale and homogenous or heterogeneous) were evaluated by qualitative elastography and shear velocity was determined quantitatively. Subsequent to orchiectomy, testicular samples were collected for histopathology analysis and thirty-six disorders were identified. Qualitative elastography revealed that normal healthy testicular tissues were homogenous and not pliable while the affected testicles had alterations in tissue stiffness and homogeneity. The values obtained for quantitative elastography of the testicular tissues were: normal/healthy - 1.30±0.12 m/s; degenerated - 0.97±0.08 m/s; atrophied - 2.00±0.35 m/s; hypoplastic - 0.82±0.2 m/s; cystic - 1.32±0.18 m/s; orchitis - 2.68±0.42 m/s; interstitial cell tumours - 3.32±0.65 m/s; sertolioma - 2.99±0.07 m/s and leydigoma - 2.73±0.37. ARFI elastography of abnormal testes proved to be an applicable and complementary technique in the diagnosis of testicular disease in dogs.
Keywords: Canine; Stiffness; Testicular disease